Gut microbiota and its impact on neuropsychiatric disorders - Magdalena Wójcik; Justyna Dąbrowska; Damian Bator; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction: Over the last few decades, the interest of microbiota- gut - brain axis has increased. It is thought to have an impact on the overall health of the host. Gut microbiota and central nervous system can communicate in different ways. The connection between them is especially interesting in case of neuropsychiatric diseases The aim of the study: The purpose of this systemic review was to collect and analyse current data of the association between gut microbiota and neuropsychitric disorders, specifically schizophrenia and bipolar disorder Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: gut microbiota, dysbiosis, schizophrenia, bipolar disorder Description of the state of knowledge: Dysregulation of microbiota is a potential factor in pathogenesis of brain disorders. Gut microbiome is thought to be an important part of not only normal brain development, but also modulation of host physiological systems. Studies show that the composition of microbiota in psychiatric diseases including schizophrenia and bipolar disorder differs from healthy individuals. Many environmental factors can change the composition of microbiota and therefore potentially contribute to the development of many disorders, including neuropsychiatric disorders. Summary:  Microbiota is a potential factor contributing to the onset or modulating the course of many illnessis, including brain disorders The subject of imbalanced microbiota composition give hope for finding etiology or improving treatment of many disorders. However, it still requires more studies.